Systemic delivery of a DUX4-targeting antisense oligonucleotide to treat facioscapulohumeral muscular dystrophy - Linde F. Bouwman; Bianca den Hamer; Anita van den Heuvel; Marnix Franken; Michaela Jackson; Chrissa A. Dwyer; Stephen J. Tapscott; Frank Rigo; Silvère M. van der Maarel; Jessica C. de Greef (Elsevier, 2021)
Facioscapulohumeral muscular dystrophy (FSHD) is one of the most prevalent skeletal muscle dystrophies. Skeletal muscle pathology in individuals with FSHD is caused by inappropriate expression of the transcription factor DUX4, which activates different myotoxic pathways. At the moment there is no molecular therapy that can delay or prevent skeletal muscle wasting in FSHD. In this study, a systemically delivered antisense oligonucleotide (ASO) targeting the DUX4 transcript was tested in vivo in ACTA1-MCM;FLExDUX4 mice that express DUX4 in skeletal muscles. We show that the DUX4 ASO was well tolerated and repressed the DUX4 transcript, DUX4 protein, and mouse DUX4 target gene expression in skeletal muscles. In addition, the DUX4 ASO alleviated the severity of skeletal muscle pathology and partially prevented the dysregulation of inflammatory and extracellular matrix genes. DUX4 ASO-treated ACTA1-MCM;FLExDUX4 mice performed better on a treadmill; however, the hanging grid and four-limb grip strength tests were not improved compared to control ASO-treated ACTA1-MCM;FLExDUX4 mice. This study shows that systemic delivery of ASOs targeting DUX4 is a promising therapeutic strategy for FSHD and strategies that further improve the ASO efficacy in skeletal muscle are warranted.